دور التعليم الإلكتروني في تطوير رأس المال الفكري للمؤسسات الاقتصادية. –دراسة ميدانية لبعض المؤسسات بسطيف – - زواوي, خالصة; بن خديجة, منصف (جامعة الوادي - University of Eloued, 2017)
The study aimed to understand the role of e-learning in the development of intellectual capital in some companies in the province of Setif through knowledge of its role in the development of intellectual capital in its three dimensions (human capital, structural capital, relational capital). Data collection from the therty’s studied companies . The SPSS program was used to analyze the questionnaire data. The study reached a number of results, the most important of which is that, there is a positive role of e-learning in the development of intellectual capital. It also provided recommendations to Responsibles of the companies.
مقال
Keywords: التعليم الإلكتروني; رأس المال الفكري; المؤسسات الإقتصادية.: E-Learning, Intellectual Capital, Economic companies in Setif.